Uganda's nascent oil sector: Revenue generation, investor-stakeholder alignment, and public policy - Steve Kayizzi-Mugerwa (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2020)
This paper discusses the political economy of oil in Uganda since the announcement of its discovery in 2006. It focuses on the dynamics of oil revenue generation (pre-commercial production) and expenditure, investor-stakeholder contestation (i.e. between bureaucrats, investors/oil companies, and domestic stakeholders), and the role of public policy. Although the Government has created several institutional and regulatory frameworks to manage oil-related revenues and ensure that oil contributes to structural transformation, Uganda is already experiencing many of the stylized facts associated with natural resource exploitation, including macroeconomic instability, rent dissipation, and, more broadly, threats of adverse impact on the environment and on local livelihoods in the oil regions. Besides these, Uganda, and similarly endowed African countries, face the economic challenges related to the global shift in recent decades towards a low-carbon development paradigm and the threatening prospect of oil investments becoming 'stranded assets'. The latter issues are not yet part of the policy conversation in Uganda.
Keywords: Q32; Q34; Q35; Q38; 330; environment; investor-stakeholder contestation; local livelihoods; oil revenue; publicpolicy